Arab Hadhrami Dan Arab Peranakan Di Malaysia - Latifah Abdul Latiff; Siti Nor Baya Yacob; Azmir Mohd Nizah; Anita Ismail; Adibah Sulaiman; Mashitah Sulaiman (Research Centre for Dakwah and Leadership, Faculty of Islamic Studies UKM, 2024)
Indexed by MyCite